The Relationship between Maternal Knowledge, Personal Hygiene, and Family Economic Status and the Incidence of Diarrhea in the Working Area of the Pekauman Public Health Center, Banjarmasin - Vitria; Ra’uf, Muhammad; Wulandatika, Darmayanti; Sundari, Sri (Fakultas Kedokteran, Universitas Papua, 2025)
Diarrhea remains a major public health problem among under-five children in Indonesia, particularly in areas with limited sanitation and disadvantaged socioeconomic conditions. Maternal knowledge, personal hygiene, and family economic status are key factors influencing the incidence of diarrhea. This study aimed to analyze the relationship between maternal knowledge, personal hygiene, and family economic status and the incidence of diarrhea in the working area of the Pekauman Public Health Center, Banjarmasin. A cross-sectional design was employed using accidental sampling, involving 40 mothers with children aged 2–5 years who visited the Pekauman Public Health Center. Data were collected using a structured questionnaire and analyzed using the Spearman Rank correlation test. The results demonstrated significant associations between maternal knowledge (p = 0.008; r = 0.412), personal hygiene (p = 0.000; r = 0.710), and family economic status (p = 0.000; r = 0.645) and the incidence of diarrhea, with personal hygiene showing the strongest correlation. This study contributes to public health practice by emphasizing the importance of integrated, family-based interventions, including strengthening maternal education, improving hygienic behaviors, and enhancing family economic capacity, to reduce diarrhea incidence at the primary health care level.